The Post-Literary, Post-Truth, and Modernity. Issue 1 (April 2019) - Corby, James
Abstract : This article argues that what might be called the 'post-literary' is the completion of the literary – specifically, the literary that came to theoretical self-realisation in what came to be called Romanticism – and that that completion, which is our contemporary reality, happens, by its very nature, at the level of politics.